Dari Konsep Ekonomi Islam Sampai Urgensi Pelarangan Riba; Sebuah Tawaran Ekonomi Islam Timur Kuran - Havis Aravik; Achmad Irwan Hamzani; Nur Khasanah (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2021)
Islamic economic thought became increasingly prevalent with the birth of various schools of thought in Islamic economics. One of them is the critical alternative school that was pioneered by Timur Kuran. This research will discuss from Islamic economics to the urgency of prohibiting usury; an offer of the East Kuran Islamic economy. With the aim of knowing and analyzing the extent to which Eastern Kuran's economic thought made significant contributions to the development of contemporary Islamic economics. This research is a qualitative research with a library research approach and all data obtained were analyzed using descriptive analysis methods. The results of this study indicate that Timur Kuran is one of the pioneers of the Critical alternative school which critically studies various concepts of Islamic economics and banking. Various forms of economic thought such as from the concept of Islamic economics are none other than modern doctrines that offer alternatives to the economic systems of Capitalism and Socialism. The emergence of an Islamic economy was none other than political-cultural, with the largest contribution coming from Pakistanis, zakat is a more effective safety net than a secular redistribution system and the waqf system does not yet have the flexibility needed for efficient resource use, and the Qur'an prohibits the practice of usury which involves compounding the debt of a loan that is unable to make payments according to a predetermined schedule.